Diabetes transitional care in a district general hospital: an audit. (24th May 2012) - Misquith, R; Nathwani, N; Rehman, T; Chhaochharia, A
Abstract : Aims: To collect information about patients experience of their transition from paediatric to young adult services To receive feedback from staff involved in the care of patients transferring from paediatric to adult care. To obtain baseline information on the specific processes currently in place at this trust for diabetic patients transferring from paediatric to adult care based on the recommendations set out by Diabetes UK and local standards. Methodology: Two survey forms were designed, one for the staff and the other for the patients to complete. In addition, baseline data on the processes currently in place for transition of patients from paediatric to adult services was collected by retrospective case notes and electronic database review. 49 patients were identified for the audit data. Survey forms were sent to all the patients. Staff survey forms were distributed to staff involved in diabetes transition. Results: 62% of patients were transferred to adult services at 17 years of age. 47% of cases transition took place at a time of relative stability and coordinated with other life transitions. 98% of cases were transferred into a dedicated adolescent clinic run jointly by paediatric and adult staff. In only 13% of the cases, a clinical psychologist was involved in the transition process. Only 27% of cases written information was provided about transition process and transition clinic. Less than 56% of patients were provided with written information about career, socialising and vocational issues. Only 40% of patients felt the age of transfer to adult services was appropriate, remaining felt it should be later Only 33% of staff felt that patients educational needs are met. Conclusion: Vast majority of the patients are being transferred through a dedicated adolescent clinic. There is a lack of written information about transition process, transition clinic as well as information about career, socialising and vocational issues. There is a need to actively involve the patient and family in transition process to ensure transition takes place at an appropriate age coordinated with other life transition.